2023
DOI: 10.1002/smll.202300871
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Nanobodies’ Bioactivity: Coupling to Ultrasmall Gold Nanoparticles Allows the Intracellular Interference with Survivin

Abstract: Nanobodies are highly affine binders, often used to track disease‐relevant proteins inside cells. However, they often fail to interfere with pathobiological functions, required for their clinical exploitation. Here, a nanobody targeting the disease‐relevant apoptosis inhibitor and mitosis regulator Survivin (SuN) is utilized. Survivin's multifaceted functions are regulated by an interplay of dynamic cellular localization, dimerization, and protein–protein interactions. However, as Survivin harbors no classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Notably, the conjugation of larger ligands to a glutathione-azide-terminated gold surface via click chemistry (CuAAC) leads to fewer ligands with a higher molecular footprint. This was found for 2 nm gold nanoparticles carrying Cy3 molecules (5 per nanoparticle, 2.5 nm 2 each), Cy5 molecules (36 per nanoparticle; 0.35 nm 2 each), FAM molecules (6 per nanoparticle, 2.1 nm 2 each), , Alexa Fluor 647 molecules (11 to 18 per nanoparticle, 0.70 to 1.15 nm 2 each), , nanobodies (5 per nanoparticle, 2.5 nm 2 each), siRNA molecules (6 to 10 per nanoparticle, 1.4 to 2.0 nm 2 each), or molecular tweezers (11 to 30 per nanoparticle, 0.42 to 1.14 nm 2 each) . A quantitative assessment of the clicking efficiency on glutathione-azide-terminated 2 nm gold nanoparticles showed that only 6 to 11 out of 118 available azide groups were used for conjugation .…”
Section: Resultsmentioning
confidence: 75%
“…Notably, the conjugation of larger ligands to a glutathione-azide-terminated gold surface via click chemistry (CuAAC) leads to fewer ligands with a higher molecular footprint. This was found for 2 nm gold nanoparticles carrying Cy3 molecules (5 per nanoparticle, 2.5 nm 2 each), Cy5 molecules (36 per nanoparticle; 0.35 nm 2 each), FAM molecules (6 per nanoparticle, 2.1 nm 2 each), , Alexa Fluor 647 molecules (11 to 18 per nanoparticle, 0.70 to 1.15 nm 2 each), , nanobodies (5 per nanoparticle, 2.5 nm 2 each), siRNA molecules (6 to 10 per nanoparticle, 1.4 to 2.0 nm 2 each), or molecular tweezers (11 to 30 per nanoparticle, 0.42 to 1.14 nm 2 each) . A quantitative assessment of the clicking efficiency on glutathione-azide-terminated 2 nm gold nanoparticles showed that only 6 to 11 out of 118 available azide groups were used for conjugation .…”
Section: Resultsmentioning
confidence: 75%
“…We therefore compared specific differentiation markers of human lung tissue to those of mouse lung and cell culture models. For the first time, we showed that tissue cells of the human lung express the inhibitor of apoptosis protein, Survivin, which is critical for mitosis and proliferation [ 31 , 56 , 57 , 58 , 59 ]. Furthermore, we implemented cell culture models that reflect the necessary characteristics of lung tissue cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the much smaller nanobodies (about 4 nm) 61 were successfully attached to ultrasmall gold nanoparticles (2 nm; carrying about 4 nanobodies each) and showed highly efficient targeting against the protein Survivin. 62 The ability to "dial in" nanoparticle-biosystem interactions fully extends to cells. HeLa cells were incubated with gold nanoparticles with 2, 4, and 6 nm cores and cationic, anionic, and zwitterionic ligands (Figure 7a), and the uptake was quantified by inductively coupled mass spectrometry (ICP-MS) (Figure 7b).…”
Section: Regulating the Interactions Of Ultrasmall Nanoparticles With...mentioning
confidence: 99%
“…As antibodies are much larger (about 12 nm) than ultrasmall nanoparticles, it does not make sense to attach them as targeting moiety to their surface. However, the much smaller nanobodies (about 4 nm) were successfully attached to ultrasmall gold nanoparticles (2 nm; carrying about 4 nanobodies each) and showed highly efficient targeting against the protein Survivin …”
Section: Introductionmentioning
confidence: 99%